Genre Analysis of Brochure Hotel in Indonesia - Nurmayana Nurmayana; Mirwana Siska (All Fields of Science Journal Liaison Academia and Sosiety, 2023)
The aim of this study was to find out the types of text are found in brochure hotel in Indonesia and to know the more dominant text are found in brochure hotel in Indonesia. The methodology adopted in this research was descriptive qualitative methods. The source of the data was taken from the texts of brochures hotel in Indonesia. This brochures are found in the famous hotel, like JW Marriot (in Medan, Jakarta), Trans Luxury (in Bandung), Hotel Inn (in Jogja) The Kuta Beach Heritage (in Bali) which using brochure to introduce the hotel. The result of the study shows that brochures hotel in Indonesia contains 13 types which include 1 types of text; Hortatory Exposition. Keywords: Genre, Brochure, Hotel.